Impact of maternal risk factors on the outcome of pregnancy in Baghdad city (Baghdad Science Journal, 2025)
To find out the impact of maternal risk factors on the outcome of pregnancy in Baghdad city. A descriptive purposive study was carried out on 100 postpartum women who had delivered for 1 hr. to 24 hrs. ago . the study sample was selected from three hospitals in Baghdad city ( Baghdad teaching hospital ,Fatima Al-Zahra'a maternity and pediatric teaching hospital and Al-Yarmook teaching hospital),during the period from 25 Jan. to 25 Feb. 2006. The data were collected through the use of questionnaire format reviewing pregnants' records and personal interview and were analyzed by using descriptive and inferential statistical approaches. The finding revealed that maternal pregnancy complications had weak effects on pregnancy outcome , while maternal employment & spouse's consanguinity were predictors for poor pregnancy outcome . The study recommended the necessity of establishing health education programs for pregnant to be self monitoring & early detection of complications that associate the pregnancy . In addition promote the system of follow up care during antenatal ,perinatal,& postnatal.